2023
DOI: 10.1093/humrep/dead042
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of BMI and age on ART outcomes

Abstract: STUDY QUESTION For a woman with infertility and overweight/obesity, can infertility treatment be postponed to first promote weight loss? SUMMARY ANSWER Advice regarding a delay in IVF treatment to optimize female weight should consider female age, particularly in women over 38 years for whom only substantial weight loss in a short period of time (3 months) seems to provide any benefit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Compared with previous studies on the relationship between BMI and IVF pregnancy outcomes, the strength of the present study is derived from an analysis that includes age, which is the most important factor determining the oocyte quality and IVF outcomes [ 10 ]. Filipa et al also studied the effect of age and BMI on ART outcomes, and the conclusions they reached were consistent with our findings [ 15 ]. The effects of obesity on pregnancy outcomes have been extensively documented [ 5 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Compared with previous studies on the relationship between BMI and IVF pregnancy outcomes, the strength of the present study is derived from an analysis that includes age, which is the most important factor determining the oocyte quality and IVF outcomes [ 10 ]. Filipa et al also studied the effect of age and BMI on ART outcomes, and the conclusions they reached were consistent with our findings [ 15 ]. The effects of obesity on pregnancy outcomes have been extensively documented [ 5 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Irritable and hyperthymic temperaments had no effect on treatment success. We also found that, besides known predictors of infertility treatment success, such as age, BMI, or previous miscarriage 39 41 , other somatic and socio-economic factors have no or minimal effect on infertility treatment outcomes, their effect, if present, being much smaller compared to that of affective temperaments.…”
Section: Discussionmentioning
confidence: 59%
“…According to a very recent study, an intervention to induce weight loss in women prior to ART appears to be beneficial, particularly in women younger than 35 years with a BMI ≥ 25 kg/m 2 . Therefore, for clinical practice, an individualized strategy that takes into account maternal age, patient’s weight, diet, and lifestyle may be the best course of action [ 142 ].…”
Section: Future Research Directions and Conclusionmentioning
confidence: 99%